Dr. Bull's Jewel: Keyboard music of John Bull (1563-1628) - Bull, John 1562-1628; Cok, Kathryn (New York Lyrichord, 2007)
John Bull was an important member of the English Virginalist School of the late 16th, early 17th centuries with the likes of Sweelinck, Gibbons and Byrd. A prolific composer of music for the keyboard, Bull composed in a variety of styles and genres, and was one of the composers who witnessed and helped create the transition from The Renaissance to the Baroque. A protege of the great Ton Koopman, New York City born Kathryn Cok won first prize in the 2001 Early Music Competition for voice, organ and Harpsichord in Brunnenthal, Austria, was harpsichordist in the European Union Baroque Orchestra, has worked with orchestras such as the Amsterdam Baroque Orchestra, Musica ad Rhenum, is a co-founder of the Anglo-Dutch ensemble Het Caecilia-Concert, and has worked with other fine and notable early music groups in Europe and North America. She has recorded for Lyrichord (Dear Friends and Gentle Hearts, LEMS 8036) and for several European labels. This is her debut solo recording.
Bull's Goodnight -- Chromatic Pavan (Queen Elizabeth's) -- Chromatic Galliard -- The King's Hunt -- Walsingham -- Bonny Peg of Ramsey -- Fantastic Pavan -- Galliard to the Fantastic Pavan -- My Self -- In Nomine -- My Jewel -- The Quadran Pavan -- Galliard to the Quadran Pavan
Keywords: 16th Century (1501-1600); Keyboard music; United Kingdom